PREPARATION OF 3D VIRTUAL GAME-BASED AUDIT SIMULATION APPLICATIONS FOR PROSPECTIVE AUDITORS - Algam Algam Octada; Adam Zakaria; Windy Permata Suyono (Research Trend in Technology and Management, 2026)
This study aims to develop a 3D virtual game-based audit simulation application as an innovative learning medium for prospective auditors. The study is motivated by the limited practical understanding of audit procedures among students due to learning methods that are still predominantly theoretical and lack real audit experience. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The developed application includes simulations of various audit procedures, such as stock taking, cash count, accounts receivable and payable confirmations, and revenue testing based on auditing standards and PSAK. The results indicate that the 3D virtual audit simulation application can improve students' learning motivation, conceptual understanding, and practical auditing skills in a more interactive and effective manner. This study is expected to support the advancement of technology-based auditing education in higher education institutions